Compliance with an individualized vs. the FIFA 11+ injury prevention program - Razi, M.; Alizadeh, M. H.; Minoonejad, H.; Meyer, T. (British Journal of Sports Medicine, 2021)
Background Players´ compliance with injury prevention programs (IPP) can significantly affect the effectiveness of such programs in injury reduction.